Visual framing analysis of typhoon Yagi in Vietnamese online newspaper - Tran Vu Thi Giang Lam; Lee, Kuok Tiung (Fakulti Kemanusiaan, Seni dan Warisan, UMS, 2024)
Typhoons or flooding during the rainy season in Vietnam are recurring issues. However, Typhoon Yagi in 2024 was the strongest unprecedented storm to hit the country in the past 30 years, causing much damage to millions of people and property. Media updates are of particular interest during such crises, helping the public stay informed about what is happening in typhoon-affected areas, especially the powerful messages conveyed through visual images. This study employs quantitative and qualitative methods to examine the photographic coverage of Typhoon Yagi in a Vietnamese online news portal. It focuses on prominent visual frames and the compositional elements of photographs, such as camera shot size, camera angles, and the messages conveyed through images. The findings reveal that the dominant frame is the economic consequences, followed by the political and human interest frames. Various camera shots and angles, including long shots, medium shots, aerial angles, and eye-level angles, were employed to capture Typhoon Yagi's images. This study aims to contribute to the limited research on visual framing in disasters, with significant implications for media studies and crisis communication.